Granular Cell Schwannoma - Dheepa R; Janaki C; Gomathy N; Sentamilselvi G; Janaki V R (Wolters Kluwer Medknow Publications, 2004)
An 11 year old female child had a small painful spot over the scalp of 4 months duration. Earlier, she had undergone a local excision for a similar problem, but it had recurred at the same site after a few months. Examination revealed a skin colored sessile tender firm papule of 3 mm size on the right parietal region. Excision biopsy showed broad fascicles of tumor cells with eosinopilic cytoplasmic granules infiltrating the dermis amongst the collagen bundles, which was consistent with granular cell schwannoma.